A Case of a Spontaneous Self-resolving Retrobulbar Hemorrhage Following 3, 4-Methylenedioxy-methamphetamine Use. Issue 4 (July 2017) - Chervenkoff, Jordan V.; Rajak, Saul N.; Selva, Dinesh; Davis, Garry
Abstract : This case report discusses the case of a 23-year-old male patient who experienced retrobulbar pain, diplopia, proptosis, and mild lower eyelid bruising after consuming 3, 4-methylenedioxy-methamphetamine. The symptoms settled over 10 days and vision returned to normal without intervention. The authors discuss the differential diagnosis relevant to the presenting complaints and propose several mechanisms linking 3, 4-methylenedioxy-methamphetamine use to spontaneous nontraumatic intraorbital hematoma. Abstract : Non-traumatic retrobulbar hemorrhage in the context of 3, 4-Methylenedioxymethamphetamine consumption: pathophysiology, differential diagnosis and treatment.